Penguasaan pelajar STAM terhadap imbuhan kata Bahasa Arab / Muhamad Fahmi Abd Jalil - Muhamad Fahmi, Abd Jalil (2012)
This research is to identify the level of students’ competency towards affixes and the word meaning of the affixed words in Arabic. The debate of affixes in Arabic covers alAf’a:l al-Mazi:d and al- Istiqa:q. This research also intends to identify the factors that affect low competency of students’ mastering towards of fixes and meaningsin Arabic and identifying the hard parts of mastering and the source of difficulties faced by students. Several effective ways or solutions in understanding and mastering affixes and meanings in Arabic are being introduced or proposed in the last chapter of this research. The research participants were selected from students who are undertaking the Malaysian Higher Religious Certificate (STAM) from several schools in Perak state. This research is a quantitative research and descriptive analysis used in analyzing results and findings. Data analysis using SPSS software version 18.0 and the findings are reported with the support of graphs, ilustrations and pie charts. The final result finds that the level of students’ mastering in affixes and the meaning of affixed words in Arabic still in weak position and will be needing full hands on in handling all the weaknesses. Few identified factors that caused the weaknesses are students’ attitude and motivation, syllabus that being offered, and less support and encouragement from the related parties. This research also opens new dimension or exposure in Arabic learning and teaching morphology. Hopefully the findings of this research will attact the attention from all parties, especially those who are directly involved in educational field or department institutions to take immediate action in increasing the students’ mastering level of competency towards Arabic language morphology and also increasing the quality and standard of Arabic language in national education.